2016
DOI: 10.15835/nbha44210304
|View full text |Cite
|
Sign up to set email alerts
|

Physico-Chemical and Antioxidant Characteristics in Fruits of Walnut (<i>Juglans regia L.</i>) Genotypes from Inner Anatolia

Abstract: Walnut fruits are used for their nutrition properties for a long time in Anatolia, where seed propagated walnuts are naturally found, as solitary individuals or dense populations. Some relevant physico-chemical and antioxidant characteristics of fruits were determined for fifteen promising walnut (Juglans regia L.) selections (named 'G-1' to 'G-15') propagated from seeds. The well-known Turkish walnut cultivar 'Sebin' was included in the analysis as a standard in order to make comparison with seed propagated g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(13 citation statements)
references
References 24 publications
(32 reference statements)
3
9
0
Order By: Relevance
“…Bakkalbasi et al [42] (2013) published a work in which DPPH values for 6 commercial local walnut cultivars in Turkey ranged from 41.91 to 85.15%. In another work, total antioxidant activity determined by TAEC method from 15 genotypes and 'Sebin' cultivar in Turkey was in the range of 93 and 128 µmol Trolox eq./g [43] (Beyhan et al, 2016). When compared to the previously published studies restricted to Turkey, our results were close to the values reported by these works.…”
Section: Resultssupporting
confidence: 86%
“…Bakkalbasi et al [42] (2013) published a work in which DPPH values for 6 commercial local walnut cultivars in Turkey ranged from 41.91 to 85.15%. In another work, total antioxidant activity determined by TAEC method from 15 genotypes and 'Sebin' cultivar in Turkey was in the range of 93 and 128 µmol Trolox eq./g [43] (Beyhan et al, 2016). When compared to the previously published studies restricted to Turkey, our results were close to the values reported by these works.…”
Section: Resultssupporting
confidence: 86%
“…The protein results were in agreement with those obtained by Koyuncu and Askin [25] who found that the protein in different walnut genotypes contents varied between 6.30 and 22.0%. Phenol contents were in good agreement with Beyhan et al [6] who found that the phenol content of different pecans was found to be in the range of 50-2,499 mg GAE/100 g %. USDA [26] determined values between 367-1,065 mg GAE/100.The total protein, oil and carbohydrate content of walnuts from Portugal were in the range of 14.38 -18.03%, 68.83 -72.14% and 3.75-6.10%, respectively [27].…”
Section: 2supporting
confidence: 89%
“…The Juglans division is widely cultivated in the temperate zone [5]. Cooling requirements for walnut trees are as low as 450-1500 hours of temperatures below 10 ° C during winter [6]. Moreover, cultivated walnut varieties are well adapted to the climatic conditions of different production areas [7].…”
Section: Introductionmentioning
confidence: 99%
“…In the past years some researchers have focused on horticultural agronomy practice ( Persic et al, 2018 ) or on basic chemical composition, e.g. fat, fatty acid ( Kumawat et al, 2017 , Ros and Mataix, 2006 ) and tocopherols ( Pérez-Fernández et al, 2017 ) or polyphenols in walnuts ( Beyhan, Gozlekci, Gundogdu, & Ercisli, 2016 ), hazelnuts ( Pino Ramos et al, 2019 ), pistachio ( Noguera-Artiaga et al, 2019 ;; Liu et al, 2014 ) or almonds ( Bolling, Dolnikowski, Blumberg, & Chen, 2010 ). Increasingly, research is focused on waste nut products ( Grace et al, 2016 ) and the importance of processing ( Lainas et al, 2016 , Monagas et al, 2009 , Pelvan et al, 2018 , Sonmezdag et al, 2019 , Stuetz et al, 2017 , Trox et al, 2010 ) or nut leaves ( Amaral et al, 2004 , Forino et al, 2016 , Pereira et al, 2007 ), rather than on the nuts themselves.…”
Section: Introductionmentioning
confidence: 99%